2019
DOI: 10.1002/prep.201800277
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Enhancement of HMX by Bonding with TiO2 Nanoparticles

Abstract: The appropriate structure and properties of a composite material, including the morphology, particle size, and bond strength, are very important for its performance and practical applications. The energetic material HMX (C4H8N8O8, cyclotetramethylenetetranitramine) is typically mixed with nanocatalysts to improve its thermal decomposition, which is advantageous for its detonation performance in practical applications. Inspired by the bioadhesion of mussels, a HMX@PDA@TiO2 (HMX first coated with PDA film and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In recent years, the core@double shell structure strategy has also been adopted in highly explosive-filled polymer composites. It has been found that the construction of the core@double shell structure is highly effective in enhancing the mechanical properties, , thermal decomposition, thermal conductivity, and energy release. In our previous work, we have successfully prepared a core@double shell-structured 1,3,5,7-tetranitro-1,3,5,7-tetrazocane (HMX)@1,3,5-triamino-2,4,6-trintrobenzene (TATB)@PDA energetic composites with reduced sensitivity and enhanced mechanical properties. Nevertheless, in order to achieve high coverage and low mechanical sensitivity, the content of the nano-TATB shell should be as high as 10% .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the core@double shell structure strategy has also been adopted in highly explosive-filled polymer composites. It has been found that the construction of the core@double shell structure is highly effective in enhancing the mechanical properties, , thermal decomposition, thermal conductivity, and energy release. In our previous work, we have successfully prepared a core@double shell-structured 1,3,5,7-tetranitro-1,3,5,7-tetrazocane (HMX)@1,3,5-triamino-2,4,6-trintrobenzene (TATB)@PDA energetic composites with reduced sensitivity and enhanced mechanical properties. Nevertheless, in order to achieve high coverage and low mechanical sensitivity, the content of the nano-TATB shell should be as high as 10% .…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that this explosive@PDA@TiO 2 structure has the effect of enhancing the thermal decomposition of HMX. In Zhu's work, TiO 2 nanoparticles were anchored on the surface of HMX by PDA coating, which decreased the decomposition onset temperature and peak temperature by about 60 • C and 35 • C, respectively [44]. However, PDA itself contributes to improving the thermal stability of EMs in many cases.…”
Section: Thermal Sensitivity and Safety Modificationmentioning
confidence: 99%
“…The strong adhesion of this bonding layer improved the bonding degree of Al/CuO. Several groups have used PDA to modify or assemble energetic materials [20][21][22][23][24]. Zhu et al have coated a shell of PDA on HMX particles in order to enhance the safety and adhesive properties of HMX when used in PBX [22].…”
Section: Introductionmentioning
confidence: 99%
“…He et al synthesized n-Al/PDA/PTFE by PDA as an adhesive layer and the reactivity of n-Al@PDA/PTFE was regulated by adjusting the thickness of PDA [25]. While some successes have been reported, many of these techniques needed to be carried out under alkaline conditions (pH 8.5) [21,[24][25][26][27]. However, Al NPs exhibit significantly higher chemical reactivity and can more readily react with water under alkaline conditions [28] In this paper, a novel, one-pot approach is proposed for the assembly of Al/PDA/CuO in a neutral aqueous solution at room temperature, which avoided energy loss due to the Al oxidation under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%